Waste plastic recovery catalyst system as well as preparation method and application thereof
By depositing Pt active components and Cu and Si regulators on the diatomaceous earth support and combining them with NaY molecular sieve to form a composite catalyst system, the problems of existing catalysts being prone to agglomeration and carbon accumulation at high temperatures are solved, and efficient cracking of waste plastics and improving oil yields are achieved.
Patent Information
- Application Number
- CN202311229483.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-22
AI Technical Summary
The existing waste plastic catalysts have problems with high amount of active components, poor dispersion, easy agglomeration and carbon accumulation at high temperatures, which makes them more difficult in industrial applications.
The surface deposition site modified diatomaceous earth is used as a support, and the Pt active components and Cu and Si regulators are loaded through gas-phase atomic deposition, and combined with the NaY molecular sieve connected in series to form a composite catalyst system.
The high dispersion and stability of Pt nanoparticles are achieved, the agglomeration effect of active metals at high temperatures is slowed down, the thermal stability and carbon deposit stability of the catalyst are improved, and the cracking activity and oil yield of waste plastics are significantly improved.
Smart Images

Figure BDA0004463410300000091 
Figure BDA0004463410300000121 
Figure BDA0004463410300000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waste plastic recycling, and in particular relates to a waste plastic recycling catalyst system and a preparation method and application thereof. Background Art
[0002] Global plastic waste has exceeded 4.9 billion tons, but less than 9% of the plastic is recycled and reused. Most of it is discarded or treated as waste. The recycling cost is high and the decomposition rate is slow, causing serious environmental pollution problems.
[0003] At present, waste plastics can be disposed of in landfill, incineration and resource utilization. Plastic resource recycling is the future trend of waste plastics disposal. Chemical recycling of plastics is to convert plastic macromolecules into small molecular products such as polymer monomers, pyrolysis oil and pyrolysis gas by chain breaking, and further use them as chemical raw materials. Compared with thermal cracking recovery, catalytic cracking of waste plastics under high temperature and catalyst conditions can further improve the oil yield and quality of the product.
[0004] CN202210444102.7 discloses a method for preparing cycloalkane aviation fuel by hydrodeoxygenation of aromatic oxygen-containing waste plastics, using a supported metal-metal oxide catalyst to catalyze the hydrodeoxygenation of aromatic oxygen-containing waste plastics in the presence of a solvent to directly prepare cycloalkane aviation fuel; CN202110847013.2 discloses a method for directly preparing aviation gasoline and aviation kerosene from polyolefin waste plastics, using high-molecular polyolefin waste plastics as raw materials, using a bifunctional catalyst composed of a precious metal and an inorganic solid acid, realizing the coupling of the hydrogenation degradation of high-molecular-weight polyolefin plastics with the isomerization reaction, and achieving a one-step The method continuously realizes the preparation of high-value oil products from polyolefin plastics; CN202110011768.9 discloses a molecular sieve catalyst for the cracking of waste plastics, its preparation method and a method for cracking waste plastics, and a modified molecular sieve composite material is prepared by calcined kaolin, water glass, a directing agent and alkali solution; by constructing a bifunctional catalyst, it is beneficial to improve the cracking activity of waste plastics, but most of the current supported bifunctional catalysts are usually prepared by traditional impregnation methods, which have the characteristics of high active component dosage, poor dispersibility, easy agglomeration of active components at high temperatures, low atomic utilization, and easy carbon deposition coverage of active components, making actual industrial application difficult.
[0005] Therefore, in view of the above difficulties, developing a catalyst with both high activity and stability is the key to achieving effective resource utilization of waste plastics. Summary of the invention
[0006] One of the purposes of the present invention is to provide a catalyst system with high activity and stability for application in the field of waste plastic resource utilization, so as to achieve effective resource utilization of waste plastic.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0008] A waste plastic recovery catalyst system, the catalyst comprising diatomite with modified surface deposition sites, Pt active components and Cu and Si regulators loaded by gas phase atomic deposition, and NaY molecular sieves connected in series in cascades; wherein the loading amounts of Pt, Cu and Si elements are 0.02-0.1%, 0.4-3% and 0.1-0.5% respectively, calculated on the mass of diatomite.
[0009] This catalyst has the following advantages: the Pt dehydrogenation active component is highly dispersed and stable on the specially pretreated diatomaceous earth carrier, the particle size of the Pt nanoparticles is concentrated at about 1nm, and the deposition of Cu and Si further stabilizes the Pt nanoparticles, weakens the agglomeration effect of the active metal at high temperature, and further improves the thermal stability of the catalyst. The dehydrogenation part of the catalyst is coupled in series with the cracking part. The dehydrogenation part realizes the pre-dehydrogenation activation of plastic macromolecules, converts saturated hydrocarbons into olefin macromolecules with higher acid catalytic activity, and the olefin macromolecules are further cracked by carbon cations under the action of molecular sieves to generate small molecular hydrocarbons, realizing the synergistic effect of hydrocarbon molecule pre-dehydrogenation and catalytic cracking, slowing down the carbon deposition of metal active components during the cracking process, and the prepared catalyst showed good activity and stability during the waste plastic cracking test.
[0010] In one embodiment of the present invention, the surface deposition site-modified diatomaceous earth is surface hydroxylation-modified diatomaceous earth.
[0011] Another object of the present invention is to provide a method for preparing a waste plastics recovery catalyst system.
[0012] A method for preparing a waste plastic recovery catalyst system, the method comprising the following steps:
[0013] S1: diatomaceous earth is surface-modified by using a hydroxylation agent to obtain a suspension of modified diatomaceous earth;
[0014] S2: filtering, washing, and drying the suspension to obtain a modified diatomaceous earth carrier;
[0015] S3: Atomic deposition of Pt, Cu, and Si elements and ligand removal are performed on the modified diatomite support to obtain SiCu@Pt / diatomite as the dehydrogenation part of the catalyst;
[0016] S4: SiCu@Pt / diatomaceous earth and NaY molecular sieve powders are pressed into tablets and loaded separately to form a composite catalyst with an upper and lower layer ladder-series structure, with the NaY molecular sieve serving as a cracking part.
[0017] In one embodiment of the present invention, the hydroxylating agent in S1 is an oxidative hydroxylating agent, preferably an aqueous solution of an alcoholamine, a weak alkaline salt, or a peroxidizing agent; preferably, the alcoholamine comprises a C2-C4 primary amine, preferably one or more of ethanolamine, diethanolamine, isopropanolamine, and propanolamine; preferably, the weak alkaline salt comprises one or more of carbonic acid, phosphoric acid, and an alkali metal salt of a C1-C7 organic acid, preferably one of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium phosphate, sodium formate, sodium acetate, sodium citrate, sodium tartrate, and sodium salicylate. or more; preferably, the peroxidizing agent comprises one or more of alkyl peroxides, peroxide salts, and peroxide acids, preferably one or more of hydrogen peroxide, isopropyl benzene peroxide, tert-butyl hydroperoxide, sodium peroxide, and peracetic acid; preferably, the mass fractions of alcohol amine, weak alkaline salt, and peroxidizing agent are 1-4%, 1-4%, and 1-5%, respectively, and the preferred content fractions are 1-2%, 1-2%, and 1-2%, respectively, based on the total mass of the oxidizing hydroxylating agent; preferably, the pH value of the aqueous solution is 8-11, and the preferred pH value is 8-10.
[0018] In the present invention, the synergistic effect of alcohol amine, weak alkaline salt and peroxidation agent can reduce the impurity deposition sites on the diatomite surface and improve the density and uniformity of isolated hydroxyl sites. The uniform distribution of isolated silanol hydroxyl groups is the prerequisite for achieving high dispersion of loaded active metals. The infrared characterization hydroxyl peak is concentrated at 3740 cm -1 With 3745cm -1 This has a very good anchoring effect for the high dispersion vapor deposition of the active components in the next step. The above synergistic effect can further give the material additional optimized performance on the basis of the basic scheme of the present invention. The synergistic effect of the above scheme can further give the material additional optimized performance on the basis of the basic scheme of the present invention, and the above scheme is a preferred scheme.
[0019] In one embodiment of the present invention, the mass ratio of diatomaceous earth to solution in S1 is 1:2-10, preferably 1:6-8.
[0020] In one embodiment of the present invention, the treatment in S1 is a hydrothermal treatment; preferably, the temperature of the hydrothermal treatment is 60-90°C, preferably 80-90°C; and the time is 1-10h, preferably 5-8h.
[0021] In one embodiment of the present invention, the hydroxyl density on the surface of diatomaceous earth in S1 is 0.35-0.55 mmol / g.
[0022] In one embodiment of the present invention, the drying temperature in S2 is 150-200° C., preferably 160-180° C., and the drying time is 4-8 h, preferably 6-8 h.
[0023] In one embodiment of the present invention, the precursors of the atomically deposited Pt, Cu, and Si elements in S3 are metal organic precursors of the corresponding elements, preferably trimethylmethylcyclopentadienylplatinum (TMPt(MeCp)), di[1-(dimethylamino)-2-propanol]copper (Cu(dmap)2), and octamethylcyclotetrasiloxane (D4), respectively; preferably, the deposition cycle of the trimethylmethylcyclopentadienylplatinum precursor in S3 is 1-10 times, preferably 1-5 times; the deposition cycle of the di[1-(dimethylamino)-2-propanol]copper precursor is 1-20 times, preferably 5-15 times; the deposition cycle of the octamethylcyclotetrasiloxane precursor is 1-10 times, preferably 1-5 times.
[0024] The above-mentioned metal organic precursor of the present invention is more likely to form a uniform Si-O-Pt monomer structure on the isolated hydroxyl site of the modified diatomite carrier, and further form Pt nanoclusters with a particle size distribution concentrated at about 1 nm, which greatly improves the atomic utilization rate of the noble metal atoms, making it have the characteristics of high dehydrogenation activity at a lower noble metal loading; through the further deposition of Cu(dmap)2 precursor and D4 precursor, the passivation of the unsaturated coordinated atoms of the Pt nanoclusters can be achieved, the occurrence of deep dehydrogenation side reactions can be slowed down, and the interaction between the Pt active components and the carrier can be enhanced, and the agglomeration effect of Pt at high temperatures can be slowed down, thereby improving the stability of the catalyst. The catalyst modified by atomic deposition is SiCu@Pt / diatomite. The metal organic precursor of the above scheme can be given additional optimized performance on the basis of the basic scheme of the present invention, and the above scheme is a preferred scheme. The above-mentioned SiCu@Pt / diatomite is an atomic catalyst system of Pt, Cu, and Si elements loaded on a diatomite carrier.
[0025] In one embodiment of the present invention, an oxidant pulse is added to S3 to remove the ligand; preferably, the oxidant is oxygen and / or ozone, preferably ozone; preferably, the pulse time of the oxidant is 20-60s.
[0026] In one embodiment of the present invention, S4 is filled with two layers of steps along the flow direction of the gas flow, the upper layer is SiCu@Pt / diatomaceous earth, and the lower layer is NaY molecular sieve.
[0027] According to the cracking mechanism of hydrocarbon carbon cations, olefin molecules are easier to crack than alkanes. The hydrocarbon macromolecules are first dehydrogenated and activated on Si@PtCu / diatomite, and the generated olefin components are further cracked into small molecular oil products in the lower NaY molecular sieve. By designing the structure of this composite catalyst in series, the sequential coordination of the dehydrogenation center and the cracking center can be achieved, which effectively slows down the coverage of the catalyst carbon deposition on the dehydrogenation active site and improves the carbon deposition stability of the catalyst. The two-layer stepped loading of the above scheme can give the material additional optimized performance on the basis of the basic scheme of the present invention, and the above scheme is a preferred scheme.
[0028] In one embodiment of the present invention, the mass ratio of SiCu@Pt / diatomaceous earth and NaY molecular sieve of S4 is 1:(1-6), preferably 1:(2-5).
[0029] In one embodiment of the present invention, the NaY molecular sieve carrier in S4 is a molecular sieve with SiO2 / Al2O3=4.8-5.4.
[0030] In one embodiment of the present invention, S4 preferably uses 20-30 mesh particles after tableting. In the present invention, the particle size can be adjusted as needed.
[0031] Another object of the present invention is to provide a use of a catalyst system for recycling waste plastics.
[0032] A use of a catalyst system for recycling waste plastics, wherein the catalyst system is the above catalyst system, or is a catalyst system prepared by the above preparation method, and the catalyst system is used for recycling waste plastics, preferably for recycling PE and PP waste plastics.
[0033] Another object of the present invention is to provide a method for recycling waste plastics.
[0034] A method for recycling waste plastics, the method adopts the above catalyst system, or the catalyst system prepared by the above preparation method, and the method adopts the waste plastic recycling catalyst system to catalytically crack the waste plastics.
[0035] In one embodiment of the present invention, the mass ratio of the catalyst system to the waste plastics in the method is 1:(10-35), preferably 1:(10-20).
[0036] In one embodiment of the present invention, the reaction temperature of thermal cracking and catalytic cracking in the method is 350-500°C.
[0037] Compared with the prior art, the beneficial effects of the present invention are:
[0038] (1) The diatomite is treated with a hydroxylation agent, which effectively reduces the impurity deposition sites on the diatomite surface and increases the density of isolated hydroxyl sites, which has a very good anchoring effect on the highly dispersed vapor deposition of the Pt active component.
[0039] (2) Loading Pt active components on surface-modified diatomite easily forms Pt nanoclusters with a particle size uniformly distributed around 1 nm, which greatly improves the atomic utilization of precious metal atoms and further deposits and passivates the unsaturated coordination sites on the Pt clusters, weakening the agglomeration effect of Pt at high temperatures.
[0040] (3) The synergistic effect of pre-activation of the dehydrogenation part and catalytic cracking of the cracking part can be achieved, which effectively slows down the coverage of the catalyst carbon deposition on the dehydrogenation active sites and improves the carbon deposition stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a TEM image of diatomite prepared in Example 1. The black dots in the image are Pt nanoparticles loaded on the diatomite. The particle sizes in the image are concentrated around 1 nm.
[0042] Figure 2 This is a TEM image of diatomite prepared in Comparative Example 1. The black block in the image is the Pt metal loaded on the diatomite. Figure 1 Compared with Pt, the dispersion is poor. DETAILED DESCRIPTION
[0043] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0044] Unless otherwise specified, the raw materials used in the examples or comparative examples can be obtained from commercial channels.
[0045] The main raw materials used in the process are as follows:
[0046] name purity factory Ethanolamine 99% Inokay Isopropanolamine 94% Inokay Abutamine 99% Aladdin Sodium carbonate 99.8% Inokay Potassium carbonate 99% Aladdin Sodium acetate 99% Inokay Hydrogen Peroxide <![CDATA[31%,H2O]]> Inokay Sodium Peroxide 93% Inokay Tert-Butyl Hydroperoxide <![CDATA[70%,H2O]]> Inokay Diatomaceous earth 545 / Inokay <![CDATA[SiO2]]> / Aladdin NaY molecular sieve <![CDATA[SiO2 / Al2O3=5.2]]> Nankai Catalyst Factory HY molecular sieve / Nankai Catalyst Factory ZSM-5 molecular sieve / Nankai Catalyst Factory
[0047] The experimental preparation equipment and characterization equipment are as follows:
[0048]
[0049] The following is an introduction to the related methods used or possibly used in the embodiments or comparative examples of the present invention:
[0050] Example 1
[0051] Preparation of Catalyst A:
[0052] 20 g of diatomaceous earth (hydroxyl density 0.31 mmol / g) was weighed and dissolved in 120 g of hydroxylation solution (1 wt % ethanolamine, 1 wt % sodium carbonate, 1 wt % hydrogen peroxide, PH = 9), and stirred in a constant temperature water bath at 80°C for 6 h for hydrothermal treatment. After the treatment, the suspension was rapidly cooled to room temperature and filtered, and washed with deionized water for multiple times until the filtrate was neutral; dried in an oven at 180°C for 6 h to obtain a diatomaceous earth carrier with surface hydroxyl modification (hydroxyl density 0.42 mmol / g); 2 g of the diatomaceous earth with surface hydroxyl modification was weighed and metal loaded by atomic deposition method. Under the deposition conditions (the pulse time of the metal precursor is 20s, and the nitrogen purge time is 120s; the pulse time of ozone is 60s, and the nitrogen purge time is 120s. The temperature of the deposition chamber is 200°C, the vacuum degree is 15kpa, and the amount of nitrogen purge during the deposition process is 200mL / min), the deposition cycles of trimethylmethylcyclopentadienylplatinum, di[1-(dimethylamino)-2-propanol]copper, and octamethylcyclotetrasiloxane are 1, 2, and 1, respectively, and the corresponding Pt, Cu, and Si metal element loadings are 0.02wt%, 0.4wt%, and 0.1wt%, respectively, calculated on the mass of diatomaceous earth. Take modified diatomaceous earth powder and NaY molecular sieve powder (SiO2 / Al2O3=5.2), press them into tablets and sieve them into 20-30 mesh particles under a pressure of 10 MPaG. Take 2g of the modified diatomaceous earth and 4g of NaY molecular sieve powder, respectively, and load them into two upper and lower layers along the direction of air flow, marked as catalyst A.
[0053] The TEM image of diatomite loaded with Pt metal in catalyst A is shown in Figure 1 It can be seen that the particle size of the loaded precious metal particles is concentrated around 1 nm, with uniform and high dispersion.
[0054] Example 2
[0055] Preparation of Catalyst B:
[0056] Weigh 20g of diatomaceous earth (hydroxyl density 0.31mmol / g) and dissolve it in 160g of hydroxylation solution (isopropanolamine 1.5wt%, sodium formate 2wt%, tert-butyl hydroperoxide 2wt%, PH=10), and stir it in a constant temperature water bath at 90°C for 8h for hydrothermal treatment. After the treatment, the suspension is rapidly cooled to room temperature and filtered, and washed with deionized water for many times until the filtrate is neutral; dry it in an oven at 160°C for 8h to obtain a diatomaceous earth carrier with surface hydroxyl modification (hydroxyl density 0.47mmol / g); weigh 2g of the diatomaceous earth with surface hydroxyl modification and perform gold deposition on it by atomic deposition method. Metal loading, under the deposition conditions (the pulse time of the metal precursor is 20s, and the nitrogen purge time is 120s; the pulse time of ozone is 60s, and the nitrogen purge time is 120s. The temperature of the deposition chamber is 200°C, the vacuum degree is 15kPa, and the amount of nitrogen purge during the deposition process is 200mL / min), the deposition cycles of trimethylmethylcyclopentadienylplatinum, di[1-(dimethylamino)-2-propanol]copper, and octamethylcyclotetrasiloxane are 5, 15, and 5, respectively, and the corresponding Pt, Cu, and Si metal element loadings are 0.1wt%, 3wt%, and 0.5wt%, respectively, calculated on the mass of diatomite. Take modified diatomaceous earth powder and NaY molecular sieve powder (SiO2 / Al2O3=4.8), press them into tablets and sieve them into 20-30 mesh particles under a pressure of 10 MPaG. Take 2g of the modified diatomaceous earth and 10g of the NaY molecular sieve powder, respectively, and load them into two upper and lower layers along the direction of air flow, marked as catalyst B.
[0057] Example 3
[0058] Preparation of Catalyst C:
[0059] Weigh 20g of diatomaceous earth (hydroxyl density 0.31mmol / g) and dissolve it in 120g of hydroxylation solution (butylamine 1.5wt%, potassium carbonate 2wt%, sodium peroxide 2wt%, PH=9), and stir it in a constant temperature water bath at 90°C for 5h for hydrothermal treatment. After the treatment, the suspension is rapidly cooled to room temperature and filtered, and washed with deionized water for many times until the filtrate is neutral; dry it in an oven at 180°C for 8h to obtain a diatomaceous earth carrier with surface hydroxyl modification (hydroxyl density 0.45mmol / g); weigh 2g of the diatomaceous earth with surface hydroxyl modification, and load it with metal by atomic deposition method, Under the deposition conditions (the pulse time of the metal precursor is 20s, and the nitrogen purge time is 120s; the pulse time of oxygen is 60s, and the nitrogen purge time is 120s. The temperature of the deposition chamber is 200°C, the vacuum degree is 15kpa, and the amount of nitrogen purge during the deposition process is 200mL / min), the deposition cycles of trimethylmethylcyclopentadienylplatinum, di[1-(dimethylamino)-2-propanol]copper, and octamethylcyclotetrasiloxane are 3, 10, and 3, respectively, and the corresponding Pt, Cu, and Si metal element loadings are 0.06wt%, 2wt%, and 0.3wt%, respectively, calculated on the mass of diatomaceous earth. Take modified diatomaceous earth powder and NaY molecular sieve powder (SiO2 / Al2O3=5.4), press them into tablets and sieve them into 20-30 mesh particles under a pressure of 10 MPaG. Take 2g of the modified diatomaceous earth and 8g of NaY molecular sieve powder, respectively, and load them into two upper and lower layers along the direction of air flow, marked as catalyst C.
[0060] Example 4
[0061] Evaluation of catalyst performance in plastic cracking:
[0062] The catalyst performance was evaluated by a self-built small test device (small series reactor, thermal cracking reactor volume 200mL, catalytic cracking fixed bed reaction tube filling volume 10mL), 60g of mixed waste plastic particles (PE:PP mass ratio of 3:1, PE molecular weight 80000g / mol, PP molecular weight 150000g / mol) were weighed and loaded into the thermal decomposition reactor. The experiment was carried out in a nitrogen atmosphere with a nitrogen flow rate of 50mL / min and a thermal decomposition temperature of 500℃. The vapor produced by thermal decomposition passed through the catalytic cracking section and condensed to obtain oil products. After the experiment, the oil products were collected and weighed, and the composition was analyzed by chromatography.
[0063] The waste plastics were commercially available plastic particles. The carbon number distribution of the products was measured by gas chromatography, using the instrument GC7890 from Agilent, USA. The test conditions were as follows:
[0064] The chromatographic column type is ZB-5HT; carrier gas: N2 (30mL / min), H2 (30mL / min), air (300mL / min); detector FID (300℃), injector (300℃), injection volume 3.5μL; using the programmed temperature mode, keep at 50℃ for 10min, then increase the temperature to 200℃ at a rate of 2℃ / min and keep for 1min, then increase to 350℃ at a rate of 5℃ / min and keep for 5min.
[0065] Table 1 Oil yields from cracking of different catalysts
[0066]
[0067] From the above data, we can see that catalyst A, catalyst B and catalyst C have better oil yield and light component yield. As the temperature increases, the light component yield increases.
[0068] Example 5
[0069] Catalyst stability assessment:
[0070] The stability of the catalyst was evaluated by continuous multiple cracking experiments. 150g of waste PE plastic and 10g of catalyst B were taken. The mass ratio of waste plastic to catalyst B was 20:1. The evaluation was carried out by thermal cracking + catalytic cracking. The experiment was carried out in a nitrogen atmosphere with a nitrogen flow rate of 50mL / min, a pyrolysis temperature of 500℃, and a catalytic cracking section temperature of 500℃. Continuous multiple cracking test evaluations were carried out. The results are shown in Table 3:
[0071] Table 3 Catalyst continuous cracking test evaluation
[0072] Continuous lysis times Oil yield (%) ≤C12 yield (wt%) 1 86.3 37.3 2 86.2 36.7 3 86.0 36.5 4 85.9 36.2 5 85.1 35.9 6 84.1 34.2
[0073] Under the test conditions, the yield of pyrolysis oil products of waste plastics obtained by continuous pyrolysis of the composite catalyst for 5 times is still above 87%, and the yield of components below carbon 12 is greater than 33%. Single gram of catalyst can process 75g of waste PE plastics, and has high pyrolysis stability.
[0074] Comparative Example 1
[0075] Preparation of catalyst D (without surface hydroxyl modification):
[0076] Weigh 20g of diatomaceous earth (hydroxyl density 0.31mmol / g) and dissolve it in 120g of water, and stir it in a constant temperature water bath at 80°C for 6h for hydrothermal treatment. After the treatment, the suspension is rapidly cooled to room temperature and filtered, and washed with deionized water for many times until the filtrate is neutral; dry it in an oven at 180°C for 6h to obtain a diatomaceous earth carrier (hydroxyl density 0.31mmol / g) without surface hydroxyl modification; weigh 2g of the treated diatomaceous earth, load it with metal by atomic deposition method, and under deposition conditions (the pulse time of the metal precursor is 20s, The nitrogen purge time is 120s; the ozone pulse time is 60s, and the nitrogen purge time is 120s. The deposition chamber temperature is 200°C, the vacuum degree is 15kpa, and the nitrogen purge volume during the deposition process is 200mL / min. The deposition cycles of trimethylmethylcyclopentadienylplatinum, di[1-(dimethylamino)-2-propanol]copper, and octamethylcyclotetrasiloxane are 1, 2, and 1, respectively, and the corresponding Pt, Cu, and Si metal element loadings are 0.01wt%, 0.25wt%, and 0.08wt%, respectively, based on the mass of diatomaceous earth. Take modified diatomaceous earth powder and NaY molecular sieve powder (SiO2 / Al2O3=5.2), press them into tablets and sieve them into 20-30 mesh particles under a pressure of 10 MPaG, take 2g of the modified diatomaceous earth and 4g of NaY molecular sieve powder, and fill them into two layers of steps along the direction of air flow, marked as catalyst D.
[0077] The TEM image of diatomite loaded with Pt metal in catalyst D is shown in Figure 2 As shown, it can be seen that the precious metal particles loaded on the diatomaceous earth without surface modification have larger particle size and poorer dispersion.
[0078] Comparative Example 2
[0079] Preparation of E catalyst (only Pt deposition):
[0080] 20 g of diatomaceous earth (hydroxyl density 0.31 mmol / g) was weighed and dissolved in 120 g of hydroxylation solution (ethanolamine 1 wt%, sodium carbonate 1 wt%, hydrogen peroxide 1 wt%, pH = 9), and stirred in a constant temperature water bath at 80 ° C for 6 h for hydrothermal treatment. The suspension after treatment was rapidly cooled to room temperature, filtered, and washed with deionized water for several times until the filtrate was neutral; dried in an oven at 180 ° C for 8 h to obtain a diatomaceous earth carrier with surface hydroxyl modification (hydroxyl density 0.42 mmol / g); the surface hydroxyl group was weighed and the suspension was cooled to room temperature, filtered, and washed with deionized water for several times until the filtrate was neutral; the suspension was dried in an oven at 180 ° C for 8 h to obtain a diatomaceous earth carrier with surface hydroxyl modification (hydroxyl density 0.42 mmol / g); the surface hydroxyl group was weighed and the suspension was stirred for 6 h in a constant temperature water bath at 80 ° C for 6 h. 2g of diatomite modified by the base was loaded with metal by atomic deposition. Under the deposition conditions (the pulse time of the metal precursor was 20s, and the nitrogen purge time was 120s; the pulse time of oxygen was 60s, and the nitrogen purge time was 120s. The temperature of the deposition chamber was 200°C, the vacuum degree was 15kpa, and the amount of nitrogen purge during the deposition process was 200mL / min), the number of trimethylmethylcyclopentadienylplatinum deposition cycles was 1, and the corresponding Pt metal element loading was 0.02wt%, based on the mass of diatomite. Take the modified diatomite powder and NaY molecular sieve powder (SiO2 / Al2O3=5.2), press and sieve the sieve particles of 20-30 mesh respectively under a pressure of 10MpaG, take the modified diatomite 2g and NaY molecular sieve powder 4g after the tableting, and load them in two layers along the flow direction of the gas flow, marked as catalyst E.
[0081] Comparative Example 3
[0082] Preparation of F catalyst (different element content):
[0083] Weigh 20g of diatomaceous earth (hydroxyl density 0.31mmol / g) and dissolve it in 120g of hydroxylation solution (ethanolamine 1.5wt%, potassium carbonate 1wt%, hydrogen peroxide 1wt%, PH=9), and stir it in a constant temperature water bath at 80°C for 6h for hydrothermal treatment. After the treatment, the suspension is rapidly cooled to room temperature and filtered, and washed with deionized water for many times until the filtrate is neutral; dry it in an oven at 180°C for 6h to obtain a diatomaceous earth carrier with surface hydroxyl modification (hydroxyl density 0.42mmol / g); weigh 2g of the diatomaceous earth with surface hydroxyl modification and load it with metal by atomic deposition method Under the deposition conditions (the pulse time of the metal precursor is 20s, and the nitrogen purge time is 120s; the pulse time of ozone is 60s, and the nitrogen purge time is 120s. The temperature of the deposition chamber is 200°C, the vacuum degree is 15kpa, and the amount of nitrogen purge during the deposition process is 200mL / min), the deposition cycles of trimethylmethylcyclopentadienylplatinum, di[1-(dimethylamino)-2-propanol]copper, and octamethylcyclotetrasiloxane are 12, 22, and 14, respectively, and the corresponding Pt, Cu, and Si metal element loadings are 0.2wt%, 4wt%, and 1wt%, respectively, calculated on the mass of diatomaceous earth. Take modified diatomaceous earth powder and NaY molecular sieve powder (SiO2 / Al2O3=5.2), press them into tablets and sieve them into 20-30 mesh particles under a pressure of 10 MPaG. Take 2g of the modified diatomaceous earth and 4g of NaY molecular sieve powder, respectively, and load them into two upper and lower layers along the direction of air flow, marked as catalyst F.
[0084] Comparative Example 4
[0085] Evaluation of catalyst performance in plastic cracking:
[0086] The catalyst performance was evaluated by a self-built small test device (small series reactor, thermal cracking reactor volume 200mL, catalytic cracking fixed bed reaction tube filling volume 10mL), 60g of mixed waste plastic particles (PE:PP mass ratio of 3:1, PE molecular weight 80000g / mol, PP molecular weight 150000g / mol) were weighed and loaded into the thermal decomposition reactor. The experiment was carried out in a nitrogen atmosphere with a nitrogen flow rate of 50mL / min and a thermal decomposition temperature of 500℃. The vapor produced by thermal decomposition passed through the catalytic cracking section and condensed to obtain oil products. After the experiment, the oil products were collected and weighed, and the composition was analyzed by chromatography.
[0087] Table 2 Oil yields from cracking of different catalysts
[0088]
[0089] By comparing the results of catalyst A with those of catalysts D and E, it can be seen that the diatomaceous earth in the composite catalyst can improve the oil yield and the yield of components below C12 after surface hydroxyl modification and atomic deposition modification.
[0090] Comparative Example 5
[0091] Evaluation of cracking performance of SiO2+NaY catalyst:
[0092] Compared with Example 2, the modified diatomaceous earth in series in Catalyst B was replaced with ordinary diatomaceous earth in this comparative example, and the rest was the same as Example 2. The cracking performance of the NaY catalyst was tested, and the results are shown in the following table:
[0093]
[0094] By comparing with catalyst B, it can be seen that the composite catalyst constructed in series has higher yield, higher processing capacity per gram and better stability.
[0095] Comparative Example 6
[0096] Evaluation of cracking performance of modified diatomite + ZSM-5 catalyst:
[0097] Compared with Example 2, the NaY in series in Catalyst B is replaced with ZSM-5 molecular sieve in this comparative example, and the rest is the same as Example 2. The cracking performance of the NaY catalyst is tested, and the results are shown in the following table:
[0098]
[0099] By comparing with catalyst B, it can be seen that the composite catalyst using NaY has higher yield and single gram processing amount and better stability than that using ZSM-5.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A waste plastic recovery catalyst system, characterized in that: The catalyst comprises diatomite with modified surface deposition sites, Pt active components and Cu and Si regulators supported by gas phase atomic deposition, and NaY molecular sieves connected in series in a cascade manner; The loading amounts of Pt, Cu and Si elements are 0.02-0.1%, 0.4-3% and 0.1-0.5% respectively, calculated on the basis of the mass of diatomite.
2. The catalyst system according to claim 1, characterized in that The diatomaceous earth with modified surface deposition sites is diatomaceous earth with modified surface hydroxylation.
3. A method for preparing the waste plastic recovery catalyst system according to claim 1 or 2, characterized in that: The method comprises the following steps: S1: diatomaceous earth is surface-modified by using a hydroxylation agent to obtain a suspension of modified diatomaceous earth; S2: filtering, washing, and drying the suspension to obtain a modified diatomaceous earth carrier; S3: Atomic deposition of Pt, Cu, and Si elements and ligand removal are performed on the modified diatomite support to obtain SiCu@Pt / diatomite as the dehydrogenation part of the catalyst; S4: SiCu@Pt / diatomaceous earth and NaY molecular sieve powders are pressed into tablets and loaded separately to form a composite catalyst with an upper and lower layer ladder-series structure, with the NaY molecular sieve serving as a cracking part.
4. The preparation method according to claim 3, characterized in that: The hydroxylation agent in S1 is an oxidative hydroxylation agent, preferably an aqueous solution of an alcohol amine, a weak alkaline salt, or a peroxidation agent; Preferably, the alcoholamine comprises a C2-C4 primary amine, preferably one or more of ethanolamine, diethanolamine, isopropanolamine, and propanolamine; Preferably, the weakly alkaline salt comprises one or more of alkali metal salts of carbonic acid, phosphoric acid, and C1-C7 organic acids, preferably one or more of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium phosphate, sodium formate, sodium acetate, sodium citrate, sodium tartrate, and sodium salicylate; Preferably, the peroxidizing agent comprises one or more of alkyl peroxides, peroxide salts, and peroxide acids, preferably one or more of hydrogen peroxide, cumene peroxide, tert-butyl hydroperoxide, sodium peroxide, and peracetic acid; Preferably, the mass fractions of the alcohol amine, the weak alkaline salt, and the peroxidizing agent are 1-4%, 1-4%, and 1-5%, respectively, and the preferred content fractions are 1-2%, 1-2%, and 1-2%, respectively, based on the total mass of the oxidizing hydroxylating agent; Preferably, the pH value of the aqueous solution is 8-11, preferably the pH value is 8-10; and / or, the mass ratio of diatomaceous earth to solution in S1 is 1:2-10, preferably 1:6-8; and / or, the treatment in S1 is a hydrothermal treatment; Preferably, the temperature of the hydrothermal treatment is 60-90°C, preferably 80-90°C; and the time is 1-10h, preferably 5-8h.
5. The preparation method according to claim 3, characterized in that: The drying temperature in S2 is 150-200° C., preferably 160-180° C., and the drying time is 4-8 hours, preferably 6-8 hours.
6. The preparation method according to claim 3, characterized in that: The precursors of the atomically deposited Pt, Cu, and Si elements in S3 are metal organic precursors of the corresponding elements, preferably trimethylmethylcyclopentadienyl platinum, di[1-(dimethylamino)-2-propanol]copper, and octamethylcyclotetrasiloxane, respectively; Preferably, in S3, the deposition cycle of the trimethylmethylcyclopentadienyl platinum precursor is 1-10 times, preferably 1-5 times; the deposition cycle of the di[1-(dimethylamino)-2-propanol]copper precursor is 1-20 times, preferably 5-15 times; the deposition cycle of the octamethylcyclotetrasiloxane precursor is 1-10 times, preferably 1-5 times; and / or, adding an oxidant pulse to S3 to remove the ligand; Preferably, the oxidant is oxygen and / or ozone, preferably ozone; Preferably, the pulse time of the oxidant is 20-60 s.
7. The preparation method according to claim 3, characterized in that: In S4, two layers of step filling are carried out along the flow direction of the gas flow, the upper layer is SiCu@Pt / diatomite, and the lower layer is NaY molecular sieve; and / or, the mass ratio of SiCu@Pt / diatomaceous earth and NaY molecular sieve of S4 is 1:(1-6), preferably 1:(2-5); And / or, the NaY molecular sieve carrier in S4 is a molecular sieve with SiO2 / Al2O3=4.8-5.
4.
8. Use of a catalyst system for recycling waste plastics, wherein the catalyst system is the catalyst system according to claim 1 or 2, or is the catalyst system prepared by the preparation method according to any one of claims 3 to 7, and the catalyst system is used for recycling waste plastics, preferably for recycling PE and PP waste plastics.
9. A method for recycling waste plastics, the method using the catalyst system according to claim 1 or 2, or the catalyst system prepared by the preparation method according to any one of claims 3 to 7, characterized in that: The method adopts a waste plastic recovery catalyst system to catalytically crack the waste plastic.
10. The method according to claim 9, characterized in that In the method, the mass ratio of the catalyst system to the waste plastic is 1:(10-35), preferably 1:(10-20); And / or, the reaction temperature of thermal cracking and catalytic cracking in the method is 350-500°C.
Citation Information
Patent Citations
A method for directly producing aviation gasoline and aviation kerosene from polyolefin waste plastics
CN113502174B
Method for preparing cycloalkane aviation fuel by aromatic oxygen-containing waste plastics through hydrodeoxygenation
CN114921261A
Method for improving catalyst activity and selectivity based on atomic layer deposition directional regulation
CN108671918A
Molecular sieve catalyst for waste plastic cracking, preparation method of molecular sieve catalyst and waste plastic cracking method
CN114713268A
Method for producing petrochemical products by using waste plastics
CN116254128A